Ci-Symmetry, [2 × 2] grid, square copper complex with the N4,N5-bis(4-fluorophenyl)-1H-imidazole-4,5-dicarboxamide ligand: structure, catecholase activity, magnetic properties and DFT calculations - Parween, Arfa; Naskar, Sumita; Mota, Antonio J.; Espinosa Ferao, Arturo; Chattopadhyay, Shyamal Kumar; Rivière, Eric; Lewis, William; Naskar, Subhendu (Royal Society of Chemistry, 2017)
A new square tetranuclear copper complex of formula Cu4(LH)4·4DMF with the dinucleating amide ligand N4,N5-bis(4-fluorophenyl)-1H-imidazole-4,5-dicarboxamide (LH3) is reported herein. This ligand and the complex have been characterized by elemental analysis, FTIR, NMR, mass and UV-visible spectroscopy, as well as magnetic and electrochemical measurements. The single crystal X-ray diffraction study showed each Cu centre in a distorted square pyramidal environment, the square plane being formed by the extended coordination of two sets (N,N and N,O) of donor atoms from pairs of different ligands. The Cu4 unit has a Ci symmetry and crystallises in the P[1 with combining macron] space group in between DMF layers. The electronic spectrum of the complex exhibits a d–d transition at 676 nm. The complex also displays mild catecholase activity in DMF solution by using 3,5-di-tert-butylcatechol as substrate. Variable temperature magnetic measurements reveal an antiferromagnetic interaction between the copper centres with two different coupling constants of −143.4 and −169.0 cm−1. DFT calculations made on a single Cu4 unit from the crystal structure corroborated the antiferromagnetic coupling, the spin density of the lower-energy broken-symmetry state being consistent with an alternating +−+− singlet state operating at low temperature.